2018
DOI: 10.3389/fpsyg.2018.01091
|View full text |Cite
|
Sign up to set email alerts
|

Relative Age Effects and Gender Differences in the National Test of Numeracy: A Population Study of Norwegian Children

Abstract: Relative age effect (RAE) refers to the phenomenon by which children born early in their year of birth perform more highly than children born later in the same cohort. The purpose of this study was to evaluate whether an RAE exists in the Norwegian numeracy test for 5th, 8th, and 9th graders (National sample of 175,760). The results showed that the RAE is consistent across 5th, 8th, and 9th graders for both boys and girls. Mean scores decreased systematically with month of birth for both genders, and the mean … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
26
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 36 publications
3
26
0
Order By: Relevance
“…In this sense, several strategies are proposed to take into account to implement Physical Education interventions according to our research questions: (1) designing and implementing Physical Education sessions based on the student’s motor competence levels, individualizing learning. Boys and girls achieve motor competence unevenly in different tasks (manual dexterity, grasping and throwing, and balancing) [ 20 , 21 , 22 ], and younger ones have less motor competence than older ones (within the same cohort) [ 29 , 38 , 39 ]; (2) design and implement Physical Education curricular tasks with a logical and organized progression that creates a challenge (we must propose tasks that are achievable by all: boys, girls, adults, and children) [ 57 ]; (3) increase motivation in physical education classes, contributing to the success of the proposed tasks (tasks should be attractive to everyone, respecting their individual tastes and motivations); (4) the time of motor experiences is a determining factor in the development of motor competence [ 58 ], so it is necessary to allow more free time to play and specific physical education during the school day for preschool children (variety of materials and appropriate practice locations) [ 6 , 59 , 60 ]; (5) use other school environments, such as recess and classroom breaks to carry out Fundamental Movement Skills-based programs [ 61 ], since the more time of practice, the better motor competence [ 32 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this sense, several strategies are proposed to take into account to implement Physical Education interventions according to our research questions: (1) designing and implementing Physical Education sessions based on the student’s motor competence levels, individualizing learning. Boys and girls achieve motor competence unevenly in different tasks (manual dexterity, grasping and throwing, and balancing) [ 20 , 21 , 22 ], and younger ones have less motor competence than older ones (within the same cohort) [ 29 , 38 , 39 ]; (2) design and implement Physical Education curricular tasks with a logical and organized progression that creates a challenge (we must propose tasks that are achievable by all: boys, girls, adults, and children) [ 57 ]; (3) increase motivation in physical education classes, contributing to the success of the proposed tasks (tasks should be attractive to everyone, respecting their individual tastes and motivations); (4) the time of motor experiences is a determining factor in the development of motor competence [ 58 ], so it is necessary to allow more free time to play and specific physical education during the school day for preschool children (variety of materials and appropriate practice locations) [ 6 , 59 , 60 ]; (5) use other school environments, such as recess and classroom breaks to carry out Fundamental Movement Skills-based programs [ 61 ], since the more time of practice, the better motor competence [ 32 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…These discrepancies with respect to gender may be due to the fact that in these studies, the relative age of the children has not been taken into account, understanding by Relative Age Effect (RAE) the fact by which children born earlier, in the year calendar within a cohort, perform better than those born later [ 29 ]. These differences may also be due to different sports practices in different geographic areas (for example, baseball in the United States) that help or difficult the development of certain types of skills [ 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…Despite this, studies that include an investigation of gender in the context of delayed school entry are surprisingly rare. One study of relative age, gender, and math achievement in Norway demonstrated that boys in the oldest quartile were over-represented in the highest achievement group, whereas girls in the youngest quartile were overrepresented in the lowest achievement group (Aune, Ingvaldsen, Vestheim, Bjerkeset, & Dalen, 2018). Similarly, Morrison et al (1997) demonstrated a significant interaction between gender and delayed entry group for mathematics achievement in Grade 1 with boys outperforming girls in the delayed entry group, but not among on-time entrants.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, all children born in the same calendar year start at the same time, yet the school year starts in August and ends in June. This means that the age difference in one single class or cohort can vary by up to a year (Aune et al, 2018). Studies have repeatedly found that differences in month of birth have a significant influence on academic achievement.…”
Section: Introductionmentioning
confidence: 99%
“…These differences are often referred to as the “birthday effect,” “month of birth effect,” “age at school entry effect,” “season of birth effect,” and/or “relative age effect” (Angrist and Keueger, 1991; Musch and Grondin, 2001; Robertson, 2011; Ponzo and Scoppa, 2014). Studies have found that relative age effects (RAEs) are both systematic and persistent in the schooling system (Jinks, 1961; Cobley et al, 2009; Aune et al, 2015, 2018; Dalen et al, 2017). More specifically, relatively younger children achieve lower scores and more often have special needs, including special education (Wallingford and Prout, 2000; Cobley et al, 2009).…”
Section: Introductionmentioning
confidence: 99%